Association Between Maternal Comorbidities and Emergency Department Use Among a National Sample of Commercially Insured Pregnant Women. (12th June 2017) - Cunningham, Shayna D.; Magriples, Urania; Thomas, Jordan L.; Kozhimannil, Katy B.; Herrera, Carolina; Barrette, Eric; Shebl, Fatma M.; Ickovics, Jeannette R.
Abstract: Objectives: Evidence suggests that, despite routine engagement with the health system, pregnant women commonly seek emergency care. The objectives of this study were to examine the association between maternal comorbidities and emergency department (ED) use among a national sample of commercially insured pregnant women. Methods: We conducted a retrospective cohort study using multipayer medical claims data maintained by the Health Care Cost Institute for women ages 18 to 44 years with a live singleton birth in 2011 ( N = 157, 786). The association between common maternal comorbidities (e.g., hypertension, gestational diabetes) and ED use during pregnancy was examined using multilevel models, while controlling for age, region, and residential zip code. Results: Twenty percent ( n = 31, 413) of pregnant women had one or more ED visit (mean ± SD = 1.52 ± 1.15). Among those who used the ED, 29% had two or more visits, and 11% had three or more visits. Emergency care seekers were significantly more likely to have one or more comorbid condition compared to those with no emergency care: 30% versus 21%, respectively (p < 0.001). Pregnant women with asthma had 2.5 times the likelihood of having had any ED visit (adjusted odds ratio [AOR] = 2.46, 95% confidence interval [CI] = 2.32–2.62). There was a significant increase in the probability (approximately 50%) of ED use among pregnant women with diabetes (AOR = 1.47, 95% CI = 1.33–1.63) or hypertension (AOR = 1.49, 95% CI = 1.43–1.55) or who were obese (AOR = 1.55, 95% CI = 1.47–1.64). Increased odds associated with gestational diabetes were more modest, resulting in a 13% increased odds of using the ED (AOR = 1.13, 95% CI = 1.07–1.18). Less than 0.6% of pregnant women ( n = 177) received emergency care that resulted in a hospital admission. The admission rate was 0.4% (189 admissions/47, 608 ED visits). Conclusions: Among pregnant women, comorbidity burden was associated with more ED utilization. Efforts to reduce acute unscheduled care and improve care coordination during pregnancy should target interventions to patient comorbidity.